The Linguistic Creation of a City in the 16th-century Polish Accounts from Travels to the Holy Land - Zarębski, Rafał (Studia Ceranea, 2020)
The article tries to describe the linguistic creation of a city in Polish 16th-century diaries from journeys to the Holy Land. During long trips, the authors visited many exotic, for the Polish traveller, cities and towns to whom they devoted a lot of space in their diaries. The analysis is based on findings of theory of linguistic image of a world and on the concept of linguistic creation and semiotic role. The author outlines the set of linguistic means used by the diarists to indicate various roles. He concludes that the image of a city presented in the analysed texts oscillates between traditional frame that has its source in the classical antiquity and modern perspective significant for the man of the Renaissance.